A catalog of the diversity and ubiquity of bacterial microcompartments - Markus Sutter (Nature Portfolio, 2021)
Bacterial microcompartments (BMCs) are organelles consisting of a protein shell in which certain metabolic reactions take place separated from the cytoplasm. Here, Sutter et al. present a comprehensive catalog of BMC loci, substantially expanding the number of known BMCs and describing distinct types and compartmentalized reactions.